Analisis Supply Chain Bisnis Kuliner Halal UMKM Kelurahan Tulusrejo - Widodo, Devita Anggraeni Citra Ayu; Merlinda, Santi (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study analyzes the supply chain of halal culinary Micro, Small, and Medium Enterprises (MSMEs) in Tulusrejo Village, Malang City, using a descriptive qualitative approach. The three MSMEs examined, namely Qurnia Sari, Van-Van Bakery, and Yamka Cookies, demonstrate a commitment to halal principles and product quality, despite facing challenges in supply chain transparency and the halal certification process. The results indicate that all three MSMEs have implemented halal standards in the selection of raw materials, production, storage, and distribution. However, they face challenges such as limited resources, market competition, and a lack of marketing innovation. Further analysis reveals that the effectiveness of the supply chain is influenced by product quality consistency, distribution strategies, and support for halal certification. Strategic recommendations include enhancing human resource capacity, optimizing digital marketing, and collaborating with stakeholders to strengthen the competitiveness of halal culinary MSMEs